INJURY AND ILLNESS SURVEILLANCE DURING THE INTERNATIONAL SAILING FEDERATION SAILING WORLD CHAMPIONSHIPS 2014. Issue 4 (1st February 2017) - Leong, Darren; Tan, Ben; Pardal, Carmen Vaz; Lin, Cindy; Kam, Jia Wen
Abstract : Background: The International Sailing Federation (ISAF) World Championships brings together eilite sailors in all 10 Olympic classes. There is increasing interest in the injury and illness patterns of sailors during a major competition, especially in the newer Olympic classes (49erFX, 49er, Nacra 17). Objective: To describe the incidence, pattern, and severity of sailing-related injuries and illnesses among competitive sailors during the International Sailing Federation Sailing World Championships 2014. Design: Prospective descriptive study using the International Olympic Committee injury surveillance system reporting forms. Team officials and medical centre doctors submitted daily surveillance reports. Setting: The International Sailing Federation Sailing World Championships, 8–21 September 2014, Santander, Spain. Patients (or Participants): All participating sailors in the International Sailing Federation Sailing World Championships 2014. Interventions (or Assessment of Risk Factors): Gender, position (helm, crew), sailing class, training volume, part of boat contributing to injury, actions performed during sailing; wind and water conditions during competition. Main Outcome Measurements: The occurrence or non-occurrence of sailing-related injuries and illnesses; the number of injuries; the site, type, cause/mechanism of injury; injury severity; and contributing factors to injury. Results: There were 67 injuries (4 per 1000 days of sailing). The 49er (24% of all injuries), 470 Men and Women (24%), and 49erFX (19%) had the highest incidence. Injuries to the hand/fingers (22% of all injuries), back (18%), and foot (12%) were most common, as were contusions (37% of all injuries), cuts/lacerations (24%), and sprains (9%). Of the 29 illnesses (2 per 100 days of sailing), 9 (31%) were gastrointestinal and 6 (21%) respiratory, while 2 (7%) were gout attacks. Conclusions: The newer Olympic classes account for a large proportion of injuries during competition. These injuries were mainly acute events, occurring more on competitions days with higher wind speeds and gusts.